Rotational medicine ball throw velocity relates to NCAA Division III college baseball player bat swing, batted baseball, and pitching velocity - Taniyama, D.; Matsuno, J.; Yoshida, K.; Pyle, B.; Nyland, J. (The Journal of Strength and Conditioning Research, 2021)
Previous studies have evaluated relationships between baseball batting or pitching and whole-body power tests such as rotational medicine ball throw velocity (RMBTV) (transverse plane), lateral-to-medial hop for distance (frontal plane), and two-legged standing broad jump for distance (sagittal plane). However, no previous report has evaluated all 3 whole-body power tests in the same study to determine their relationship to bat swing velocity or pitching velocity. The purpose of this descriptive study was to determine correlational relationship strength between bat swing velocity, batted baseball velocity, and throwing velocity with 2-legged standing broad jump for distance, lateral-to-medial jump for distance, and RMBTV whole-body power tests in collegiate baseball players. Thirty-five NCAA Division III players (15 pitchers and 23 hitters; 3 players played pitcher and other positions) participated in this study. An alpha value of p < 0.05 was selected to indicate statistical significance. Moderate relationships were observed between bat swing velocity and RMBTV (r = 0.65, p = 0.003), explaining 39% of the variance, and between pitching velocity and RMBTV (r = 0.62, p = 0.02), explaining 38% of the variance. A moderate correlation was also observed between batted baseball velocity and RMBTV (r = 0.53, p = 0.02), explaining 28% of the variance. Only the RMBTV whole-body power test displayed significant relationships with bat swing velocity, batted baseball velocity, and pitching velocity. Significant relationships were not identified for either the two-legged standing broad jump for distance or the lateral-to-medial jump for distance whole-body power tests and bat swing velocity or pitching velocity. Further studies should evaluate whether the coordination developed during RMBTV movements can decrease baseball shoulder and elbow injuries associated with repetitive, poorly timed, sequential lower extremity-trunk-upper extremity whole-body movements.